Pompe disease, a late-onset - misleading form of diagnosis in a patient with persistent hepatic cytolysis syndrome - Smaranda Diaconescu; Cristina Rusu; Laura Bozomitu; Alina Costina Luca; Ecaterina Vlad; Oana-Larisa C; Ramona Babici; Silvia Strat; Lorenza Donea (Amaltea Medical Publishing House, 2020)
The article discusses a clinical case of late-onset Pompe disease in a 15-year and 6-month-old adolescent hospitalised in a Paediatric Gastroenterology department to investigate persistent liver cytolysis, without response to hepatoprotective therapy. After excluding viral, autoimmune, metabolic and toxic drug aetiologies, a storage disease was suspected and imposed biochemical and genetic tests which confirmed a type II glycogenosis (Pompe disease), both by α-glucosidase (GAA) deficiency, as well as by the identification of two gene mutations on 17q25.2-q25.3 chromosome.